Les espaces périurbains : une marge urbaine à soigner ou une nouvelle banalité territoriale ? - Xavier Desjardins (Bulletin de l’Association de Géographes Français)
There is a sharp political and media interest for outer suburbs in France. These spaces are sometimes considered as margins, not only because they are located on the edge of the agglomerations, but also because they are characterized by three processes: an undergone social marginality, territorial characteristics that could reinforce this social marginalization and, finally, a heavy environmental footprint. But, are these outer suburban spaces to be considered as a marginality to be cured or as places to be valued to develop a new kind of urban life?